Imperfect banking competition and macroeconomic volatility: A DSGE framework - Jiaqi Li (Bank of Canada, 2021)
This paper studies the impact of imperfect banking competition on aggregate fluctuations using a DSGE framework that features a Cournot banking sector. The paper highlights a new propagation mechanism of imperfect banking competition that operates via the dynamics of the expected marginal product of capital. Since capital is partly financed by bank loans, a higher expected return on capital implies that firms are more willing to borrow to invest in capital, making their capital and thus loan demand more inelastic. Market power enables banks to take advantage of the lower loan demand elasticity by charging a higher loan rate markup. Given that different shocks affect the dynamics of the expected return on capital differently, this paper finds that while the loan rate markup after a contractionary monetary policy shock increases and thus amplifies aggregate fluctuations, the impact of imperfect banking competition after a productivity shock is less clear and depends on the persistence of the shock.
Keywords: E44; E32; G21; L13; 330; Business fluctuations and cycles; Financial institutions; Interest rates